The problem of the “border” in the anarchist discourse - Martynov, Mikhail (Przegląd Wschodnioeuropejski, 2019)
The subject of this paper is the problem of the “border” in the anarchist discourse. The analysis is based on a number of key texts written primarily by Russian anarchists from the end of the nineteenth century to the beginning of the twenty-first century. The author also examines some of the texts of contemporary American anarchism. The main attention is paid to three different aspects of the conceptualization of the “border” in the anarchist discourse: the anarchist idea of travel, the problem of the “border” in the context of the Russian languagespecific view of the world, as well as the “border” as a phenomenon of the text.